PEMBELAJARAN SOMAMUN MELALUI METODE BERNYANYI PADA ANAK USIA DINI DI TK SIMAHATE TAKENGON - hermawati hermawati; Suyadi Suyadi (Pendidikan Guru PAUD, FKIP, Universitas Muhammadiyah Tasikmalaya, 2020)
ABSTRACT Religious learning is the most important thing to be taught to early childhood, one of them is like learning to pray and eat and drink properly, where early age is the golden age of children, this age is very good for stimulating religious learning in children because children can record all learning is given by kaffah. Cultivation of religious values ??must be given continuously and accustomed to children. Based on observations in the Takengon community, millennial children are now proud to pray in the mosque, and they are also reluctant to sit when eating and drinking, which can be observed when the child has stepped into adolescence, the child will not stop praying and eat irregularly. This all depends on the education experienced at preschool age. There are several factors that influence this are the child's self-factors, and environmental factors. Seeing that, we really hope that teachers can apply religious teachings, especially prayer and eating and drinking (SOMAMUN) right at an early age.